(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2017)
The aim of this study was to evaluate the efficacy of a heart rate variability biofeedback-training device in reducing stress and anxiety levels in athletes. Study participants where athletes of a handball team from a city of the state of São Paulo, Brazil. The biofeedback software used was EmWave® Desktop PC and its effects where assessed by the following instruments: The World Health Organization Quality of Life-BREF (WHOQOL – BREF), Beck Anxiety Inventory (BAI), Inventory of Stress Symptoms for Adults (ISSL), and Competitive State Anxiety Inventory (CSAI-2). There was an improvement of quality of life and reduction of stress and competitive anxiety, suggesting the efficacy of biofeedback training as a therapeutic tool for athletes.